A randomized trial of 13-Cis retinoic acid in children with advanced neuroblastoma after high-dose therapy - Kohler, J A (Nature Publishing Group, 2000)
One hundred and seventy-five children with Stage 3 or 4 neuroblastoma who had obtained a good response to conventional therapy were randomly allocated to 13-Cis retinoic acid at a dose of 0.75 mg/kg/day or placebo for up to 4 years. Toxicity was mild but no advantage in event-free survival was shown for the children receiving retinoic acid. © 2000 Cancer Research Campaign